Biopolymers from waste biomass and its applications in the cosmetic industry : A review - Gupta, Shreya; Sharma, Swati; Kumar Nadda, Ashok; Saad Bala Husain, Mohamed; Gupta, Arun Kumar (Elsevier Ltd, 2022)
The utilization of cosmetics is not a recent practice. In ancient times, kohl was used by women to darken their eyelids, also, milk is used during bathing to get soften and whiten skin. Cosmetics have a huge market all over the world, and a business of billion dollars per annum. An extensive variety of ingredients involves polymers, minerals, chemicals, and also other materials like preservatives, color, pH stabilizers, emulsifiers, and thickeners to convey anticipated characteristics to the cosmetics products. Over the past years, biopolymeric materials have gained a lot of attraction in the global cosmetics industry because of their price, durability, and adaptability. Consumer awareness concerning the harmful influence of synthetic polymers on the atmosphere guides the path for biopolymer development from natural sources. Cosmetic polymers are utilized for the nanoparticle's preparation for the fragrance's delivery. Also, nanoparticles have been loaded with dermal permeation enhancers to enhance their bioactivities on the skin. Natural polymers in cosmetic formulations are of specific significance due to their eco-friendly, safe, and biocompatible characteristics. These formulations are appropriate for a number of applications such as hair, skincare, and make-up as they are highly attractive and marketable to consumers. In this review, the applications of biopolymers such as starch, chitosan, cellulose, collagen, keratin, Polyhydroxyalkanoates (PHA), etc., in cosmetic and cosmetic packaging are discussed.